2022
DOI: 10.1136/annrheumdis-2021-221640
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and effectiveness of the IL-12/23 pathway inhibitor ustekinumab or tumour necrosis factor inhibitor treatment in patients with psoriatic arthritis: 1-year results from the real-world PsABio Study

Abstract: ObjectiveWe evaluated real-world treatment persistence and effectiveness at 1 year following initiation of IL-12/23 inhibitor ustekinumab or a tumour necrosis factor inhibitor (TNFi) for psoriatic arthritis (PsA).MethodsPsABio (NCT02627768), a prospective, observational study, followed patients with PsA prescribed first-line to third-line ustekinumab or TNFi. Drug persistence, effectiveness (achievement of clinical Disease Activity Index for Psoriatic Arthritis (cDAPSA) low disease activity (LDA)/remission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
(61 reference statements)
2
17
0
Order By: Relevance
“…The similarity in drug persistence observed here for ustekinumab and TNFi, after 3 years of follow-up, is consistent with our findings from the 1-year analysis 24. Previously it was shown that female sex, older age, chronic widespread pain, depression, high number of comorbidities and later line of bDMARD treatment reduce persistence 15 24 33 34.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The similarity in drug persistence observed here for ustekinumab and TNFi, after 3 years of follow-up, is consistent with our findings from the 1-year analysis 24. Previously it was shown that female sex, older age, chronic widespread pain, depression, high number of comorbidities and later line of bDMARD treatment reduce persistence 15 24 33 34.…”
Section: Discussionsupporting
confidence: 91%
“…Patients on ustekinumab monotherapy (without MTX) and those on TNFi+MTX combination therapy persisted longer than patients on ustekinumab+MTX combination therapy and those on TNFi monotherapy, respectively. That patients on ustekinumab monotherapy persisted longer than those on TNFi monotherapy, is consistent with our 1-year results 24. This may be due to several reasons: patients treated with a TNFi may more frequently develop neutralising antidrug antibodies, especially without MTX co-therapy, but with ustekinumab the risk of such antidrug antibodies is described as minimal 39.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One RCT of the JAKi tofacitinib in PsA also included adalimumab as an active comparator, suggesting numerically similar effect sizes 7. Further, a substantial number of observational studies have attempted comparisons of effectiveness in routine care across several different drug classes 8–15. Within the Nordic countries, we have previously shown similar treatment retention and 6-month response in patients with PsA treated with secukinumab and adalimumab 16…”
Section: Introductionmentioning
confidence: 90%
“…However, the best therapeutic approach for treating enthesitis in PsA remains unclear. In the PsABio real-world multicentre observational study, outcomes and persistence at 6-month and 1 year were similar for ustekinumab and TNF-inhibitors in PsA (Gossec et al, 2022;Smolen et al, 2021).…”
Section: Ustekinumab (P40)mentioning
confidence: 93%